THE ISSUES OF ACCESS TO JUSTICE IN THE CASE OF DISPUTE RESOLUTION WITHIN THE INDIGENOUS COMMUNITY OF TULEHU, CENTRAL MALUKU - Nurtjahyo, Lidwina Inge (UI Scholars Hub, 2011)
This study is aimed to analyze how customary law is practiced in strategizing dispute settlement among the villagers. In some cases, the parties who had the disputes brought their cases to the non states intermediaries to give the best remedies that fulfill their own senses of justice. As we know in the Access to Justice approaches, the disputes could be solved not only using both with state law and non-state law. These facts showed how people doing law community members in relation to dispute resolution mechanism based on customary law from the perspective of access to justice. By applying customary law, the indigenous communities could settle their disputes and reach a solution that satisfies their sense of justice. This paper attempts to describe and analyze the mechanisms of dispute settlement within the indigenous peoples of Tulehu, Central Maluku based on their customary law. This paper is based on a research paper titled 'Customary Criminal Dispute Resolution of Indigenous Peoples in Central Maluku.' The focus of this paper is the analysis of the strategies implemented by the community members in Tulehu, Central Maluku in relation to dispute settlement mechanism based on their customary law from the perspective of access to justice.